A real‐time light‐scattering technique for tailings solids measurement. Issue 3 (5th April 2021) - Gupta, Manisha; Ho, Tim; Srivastava, Tulika; Junaid, Abu; Sedgwick, Andrea; Tsui, Ying Y.
Abstract: This study presents the concept of an economic in situ light‐scattering sensor for real‐time measurement of the solid content in tailings facilities. An experimental setup using a blue (405 nm wavelength) laser diode and silicon photodiodes was constructed to measure the angular distribution of the intensity of scattered light. It was found that the angular intensity of scattered light for tailing samples follows a cos n (θ) relation with n  ≈ 1.5, where θ is the angle between the laser beam and the photodiode. An angular value of θ = 20° was chosen for the sensor design based on a high signal‐to‐noise ratio. The setup was used to determine the relation between scattered light intensity and solids content using a thickened tailings underflow from an oil sands facility and Kaolin as a model material. It was observed that the intensity of scattered light tends to increase with an increase in solids content, with qualitatively similar settling behavior for the two materials but at largely different time scales. An insertion‐based prototype was built and tested in a large (2.7 m height) settling column with treated mature fine tailings, and the light‐scattering data were verified by standard gravimetric method and gamma‐ray measurements. In general, good agreement was established between these measurements in the absence of optical fouling, which demonstrates the potential of the sensor as an effective tool for tailings management. Core Ideas: We developed an in situ photonic sensor for real‐time measurement of the solid content in tailings facilities. The sensing technique is based on the relation between scattered light intensity and solids content of tailings. Light scattering data was compared with gravimetric method and gamma‐ray measurements. The sensor uses low‐cost light sources and detectors for measurement that can be used at different heights. Laboratory‐scale and pilot‐scale experiments were carried out.